Restricting Of the Federal Constitution on The Constitutions of The Provinces. The Constitution of The Republic of Iraq for The Year 2005 As A Model: An analytical study - Soran Ali Hasan; Hemin Ibrahim Qadir; Adnan Amin Qadir (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
Following the change of political system in 2003, the Republic of Iraq adopted federalism as a new political system in Iraq. The Federal Constitution has recognized the entity of the Kurdistan Region as a federal region and then guaranteed its right to establish its own constitution. Beside regulating relationship between the ruler (the government) and the ruled (people), the importance of KR-I constitution becomes evident due to the special situation of KR-I in Iraq and also to create a supreme law in the region outlining the structure and powers of authorities, and how to be exercise and fully respected by the authorities of the region and the federal government too. The establishment of a regional constitution in federal systems in general is beset by several legal and practical difficulties because the regional constitution must be consistent with the provisions of the federal constitution and practically the federal and regional authorities are likely to clash or encroach on others’ authorities. This research analyzes the consistency of the KR-I’s Constitution (draft) especially with the basic principles, enumerated powers of the federal government and, the rights and freedoms of individuals stipulated in the Iraqi Constitution. It acknowledges that any violation of the provisions of the Iraqi Constitution opens the road for the Federal Supreme Court to review and abolish the inconsistent provisions in the KR-I Constitution and the Supreme Constitutional Court in KR-I may not be able to do much to protect the Constitution of the region in such cases